Optimasi Formulasi Nanopartikel Gel Ekstrak Etanol Kayu Secang (Caesalpinia Sappan L.) Sebagai Antibakteri Terhadap Propionibacterium Acnes: Optimasi Formulasi Nanopartikel Gel Ekstrak Etanol Kayu Secang (Caesalpinia Sappan L.) Sebagai Antibakteri Terhadap Propionibacterium Acnes - Maharani, Zahra Febriana; Akbar, Nanda Dwi; Priamsari, Margareta Retno (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Nanoparticle gel is a colloid consisting of nanometer-sized particles made from cosmetic active ingredients or other materials that are evenly distributed in a gel matrix. The purpose of this study was to determine the antibacterial activity of nanoparticle gel preparations of sappanwood extract against Propionibacterium acnes. The sappanwood extract was extracted by remaceration 70% ethanol then the extract was tested for antibacterial activity at concentrations of 20, 40, 60, and 80% using Nutrient Agar media against P. acnes. The results showed that the minimum inhibitory concentration of sappanwood extract appeared at a concentration of 20%. Spreadability and adhesiveness were 5.90 ± 0.06 and 14.96 ± 0.01, respectively. The results of the statistical analysis test with one sample t-test showed a p value> 0.05 so that the response of spreadability and adhesiveness between predictions was not significantly different from the actual. The optimal formula of sappanwood extract gel nanoparticles has moderate antibacterial activity against P. acnes.